No more blanket for Lambkin! - Ford, Bernette G. (Boxer Books Ltd. ; Distributed in the U.S. and Canada by Sterling Pub. Co., 2009)
Ducky wants to play laundry day and wash Lambkin's blanket. But an unexpected event occurs when the blanket is washed.